2023
DOI: 10.3390/jmse11020268
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Cavitation Flow and Pressure Pulsation of Bi-Directional Pump

Abstract: A bi-directional pump is designed by using S-shaped hydrofoil, is the most convenient way to achieve bi-directional operation. In this paper, high-speed photography is used to visualize the flow field characteristics of the bidirectional pump under different cavitation numbers, and the flow field changes caused by cavitation are quantitatively analyzed in combination with the pressure pulsation sensor. The results show that the operation efficiency of the bidirectional pump in reverse operation is lower than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The high rotating speed of blades produces local cavitation when a CFF operates underwater [37], which dramatically induces unstable, irregular, and random changes in the lift and thrust and thus greatly affects the efficiency of the CFF. This is a fatal problem for the propeller of submersible aircraft.…”
Section: Cff Operating Underwatermentioning
confidence: 99%
“…The high rotating speed of blades produces local cavitation when a CFF operates underwater [37], which dramatically induces unstable, irregular, and random changes in the lift and thrust and thus greatly affects the efficiency of the CFF. This is a fatal problem for the propeller of submersible aircraft.…”
Section: Cff Operating Underwatermentioning
confidence: 99%
“…It was found that liquid-loaded noise has higher sensitivity to the change in cavitation, and the signal spectrum is concentrated in the 2000~3000 Hz range and below 100 Hz, which is suitable for large pumps. The effect of cavitation on pressure pulsation needs to be combined with flow conditions and location [99]. The research on the pressure pulsation characteristics induced by cavitation in the pump mainly focuses on four parts: inlet, outlet, volute, and impeller.…”
Section: Combination Of Noise Measurement and Vibrationmentioning
confidence: 99%
“…Han et al [5,6] applied large eddy simulation in conjunction with the Zwart-Gerber-Belamri cavitation model to numerically analyze turbulent cavitation flow near the tip clearance of a propulsion pump. In the experiment, Liu et al [7]. used high-speed photography and pressure pulsation sensors to study tip clearance cavitation in a bidirectional axial flow pump station.…”
Section: Introductionmentioning
confidence: 99%